Dearomatization of α-Unsubstituted β-Naphthols - Li, Ying; Feng, Kongling; Zhao, Ruinan; Zhu, Cuiju; Xu, Hao (Synlett, 2023)
This Account summarizes the highly appealing dearomatization reactions of β-naphthols for the synthesis of highly functionalized, three-dimensional structures starting with simple planar aromatic compounds. The reactions are categorized mainly from the viewpoint of the construction of carbon–hydrogen, carbon–carbon, and carbon–hetero bonds (C–N/O, C–Cl, C–F) at the α-position of β-naphthols. The dearomatized products play an important role in organic synthesis and materials science.1 Introduction2 Construction of Carbon–Hydrogen Bonds at the α-Position of β-Naphthols3 Construction of Carbon–Carbon Bonds at the α-Position of β-Naphthols4 Construction of Carbon–Nitrogen/Oxygen Double Bond at the α-Position of β-Naphthols5 Construction of Carbon–Carbon and Carbon–Oxygen Bonds at the α-Position of β-Naphthols6 Construction of Carbon–Halogen Bonds at the α-Position of β-Naphthols7 Conclusion
Keywords: β-naphthol; dearomatization; naphthalen-2-one